Influence of the Angle of Inclination of the Plasma Flow of Carbone to the Substrate on the Electrical Capacitance and Morphology of the Surface of Carbon Coatings. - Glukhov, O. V.; Sudzhanskaya, I. V.; Poplavsky, A. I.; Goncharov, I. Yu. (My University, 2017)
Carbon film was obtained by pulsed vacuum-arc method on the silicon wafers. Method of impedance spectroscopy was obtained results change of electrical capacitance of parameters obtained carbon films. Morphology of surface produce by scanning probe microscopy methods was investigated. Determine correlation dependence between electrical capacity of carbon films and morphology surface against condition theirs obtainment. The explanation of the obtained results was proposed.
Keywords: Carbon films; Electrical capacity